MIE DARI TEPUNG KOMPOSIT (TERIGU,GEMBILI (Dioscorea esculenta), LABU KUNING) DAN PENAMBAHAN TELUR - STP, MP, Rosida; W, Rizky Dwi (REKAPANGAN, 2012)
Noodles is a very popular food product which is liked by many people. The rare of wheat as a raw  material  of  noodles  in  Indonesia  caused  the  research to  use  composite  flour  (wheat  flout, Gembili  flour,  and  pumpkin  flour)  to make  dried  noodles.The  aim  of this  research  was to determine the effect of the proportion of wheat flour: gembili flour and the addition of eggs to the quality of dried noodles.This research  used Completely Randomized Design (CRD) factorial pattern with 2  factors and 3 times repetition. Factor I was the proportion of wheat flour: gembili flour (80:20, 70:30, 60:40). Factor I was the  addition  of eggs (15%, 20%, and  25%). The  best treatment is the  proportion  of wheat  flour: gembili flour (70:30) and the  addition  of eggs 20% which produces dry noodles with 8.7966% of moisture content, 10.8588% of protein content, 58.8260% of starch content, 25.0062% of elasticity,  52.7117%  of   water  rehydrating  capacity,  2.8803% antioxidant  activity,  total  score  of texture preference  (86), color preference ( 82) and taste preference (71).Keywords : noodles, gembili, wheat, pumpkin, egg